1982
DOI: 10.1159/000309179
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophia retinae pigmentosa, Fundus flavimaculatus and Stargardt’s Disease in One Family

Abstract: This paper describes a family, the propositus of which suffers from dystrophia retinae pigmentosa combined with fundus flavimaculatus and Stargardt’s disease. The patient’s mother and a maternal uncle suffer from a dystrophia retinae pigmentosa, whereas a sister shows peripheral degenerations. A further sister has a scotopic b wave of the ERG of low amplitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, Fonda and Gardner [10] examined 88 patients and found only 14% myopia and stated that the refraction of these patients was not significantly different compared to a normal population. In earlier case studies, emmetropia [19,20] and low myopia [21][22][23] has been found. Stargardt [1] observed that eyes with all kinds of refractions can be affected.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, Fonda and Gardner [10] examined 88 patients and found only 14% myopia and stated that the refraction of these patients was not significantly different compared to a normal population. In earlier case studies, emmetropia [19,20] and low myopia [21][22][23] has been found. Stargardt [1] observed that eyes with all kinds of refractions can be affected.…”
Section: Discussionmentioning
confidence: 94%
“…Typically, the red-green defect is on the red side [30][31][32] described as pseudoprotanomaly or Verriest acquired type I red-green defect [33]. However, there are several studies which report green defects in Stargardt's disease [23,26,34,35]. Most of the studies only report red-green defects without defining them either to the red or to the green side [10,19,20,24,27,36].…”
Section: Discussionmentioning
confidence: 99%
“…Sorsby [1] described an adolescent boy with RP and central macular dystrophy in 1940. and a cluster of cases in another family in 1941 [2], A case of RP associated with macular dystrophy in a 31-year-old man was reported by François and Berman de Scggiaro [3] : the ERG was subnormal. Charney et al [4] documented a case of Stargardt's macular dystrophy and RP in a 16-year-old black male student, while Van Meel and Winkelman [5] reported a family in which RP. FFM and Stargardt's disease were all associated.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature only a few cases have been described in which the two disorders are associated [1][2][3][4][5]. Al though pigmentary type alterations with clumps of pigment scattered across the retina are frequently observed in FFM, the electroretinographical changes are slight, whereas they are severe in RP.…”
mentioning
confidence: 99%
“…The patient had 20/20 visual acuity; the haziness of the right eye angiogram is due to opacity of the lens nucleous. found associated with retinitis pigmentosa (van Meel & Winkelman 1982;Fiore et al 1987). A mitochondria1 DNA mutation (nucleotide position 15257), which mainly induces Leber's hereditary optic neuropathy, may also trigger Stargardt disease/fundus flavimaculatus (Heeher & Johns 1993).…”
Section: Case Reportsmentioning
confidence: 99%